Ocorrência e dosagem de açucares em algumas variedades brasileiras de feijão (Phaseolus vulgaris L.) - Fonseca, Homero; Arzolla, Jose D.P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
Sugars present in some Brazilian varieties of common beans (Phaseolus vulgaris L.) were studied by two-dimension paper chromatography with the following pair of solvente: 1) phenol-water-amonia, 80: 20: 0,5 (w/v/v/ and 2) butanol-acetic acid-water, 40: 10: 5 (v/v). Determinations were made by elution of the spots followed by colorimetry. The sugars identified and measured were raffinose, sucrose, melibiose, glucose and fructose. The more abundant sugars were fructose and glucose.